Occurrence, genetic diversity, and recombination of maize lethal necrosis disease-causing viruses in Kenya - Mwatuni, F.M.; Nyende, A.B.; Njuguna, Joyce N.; Xiong, Z.; Machuka, Eunice M.; Stomeo, Francesca (Elsevier, 2020)
Maize is the most important food crop in Kenya accounting for more than 51 % of all staples grown in the country. Out of Kenya's 5.3 million ha total crops area, more than 2.1 million ha is occupied by maize which translates to 40 % of all crops area. However, with the emergence of maize lethal necrosis (MLN) disease in 2011, the average yields plummeted to all-time lows with severely affected counties recording 90–100% yield loss in 2013 and 2014. The disease is mainly caused by Maize chlorotic mottle virus (MCMV) in combination with Sugarcane mosaic virus (SCMV) or other potyviruses. In this study, a country-wide survey was carried out to assess the MLN causing viruses in Kenya, their distribution, genetic diversity, and recombination. The causative viruses of MLN were determined by RT-PCR using virus-specific primers and DAS-ELISA. Next-generation sequencing (NGS) data was generated, viral sequences identified, genetic diversity of MLN viruses was determined, and recombination was evaluated. MCMV and SCMV were detected in all the maize growing regions at varying levels of incidence, and severity while MaYMV, a polerovirus was detected in some samples through NGS. However, there were some samples in this study where only MCMV was detected with severe MLN symptoms. SCMV Sequences were highly diverse while MCMV sequences exhibited low variability. Potential recombination events were detected only in SCMV explaining the elevated level of diversity and associated risk of this virus in Kenya and the eastern Africa region.